Consumerism and American girls' literature, 1860-1940 - Stoneley, Peter (Cambridge University, 2013)
In Consumerism and American Girls' Literature, Peter Stoneley looks at how women fictionalised for the girl reader ways of achieving a powerful social and cultural presence. Covering a wide range of works and writers, this book will be of interest to cultural and literary scholars alike.